PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING PADA MATA PELAJARAN MATEMATIKA DI KELAS 2 SEKOLAH DASAR - Hati, Hikmah; Alamsyah, Trian Pamungkas; Firdaus (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This study aims to describe the development process, feasibility, and response of students to the Development of LKPD Based on Problem Based Learning. The research method used is Research and Development (R&D) with a research design according to Borg and Gall which has been modified by Sugiyono into 6 stages, namely problem analysis, data collection, product design, design validation, design revision, and product trials. This research process is adjusted based on the research design used. Based on the feasibility results obtained, namely the results of expert validation, the material obtained a percentage of 89.6%, including in the very feasible category. The results of the validation of linguists obtained a percentage of 83.3% included in the very decent category. The results of the validation of design experts obtained a percentage of 92% included in the very decent category. Based on the results of student responses after using LKPD obtained a percentage of 98.8% included in the very decent category. Based on the results of comprehension tests conducted by students after using LKPD-based Problem Based Learning obtained a percentage of 94.6% included in the very good category